Amphiregulin is Not Essential for Induction of Contact Hypersensitivity - Akiko Yagami; Naoki Kajiwara; Keisuke Oboki; Tatsukuni Ohno; Hideaki Morita; Susan W Sunnarborg; Ko Okumura; Hideoki Ogawa; Hirohisa Saito; Susumu Nakae (Allergology International, 2010)
ABSTRACT: Background: Amphiregulin (AR) is expressed in Th2 cells, rather than Th1 cells, and plays an important role in Th2 cell/cytokine-mediated host defense against nematodes. We also found earlier that AR mRNA expression was strongly upregulated in inflamed tissue during Th2 cell/cytokine-mediated fluorescein isothiocyanate (FITC)-induced contact hypersensitivity (CHS), suggesting a contribution of AR to the induction of those responses. Methods: To elucidate the role of AR in the induction of FITC- or dinitrofluorobenzene (DNFB)-induced CHS, AR-deficient mice were sensitized and/or challenged with FITC or DNFB epicutaneously. The levels of FITC- mediated skin dendritic cell (DC) migration and FITC-specific lymph node cell proliferation and cytokine production were assessed by flow cytometry, [3H]-thymidine incorporation and ELISA, respectively, after FITC sensitization. The degree of ear swelling, the activities of myeloperoxidase (MPO) and eosinophil peroxidase (EPO) in inflammatory sites and the levels of FITC-specific immunoglobulin (Ig) in sera were determined by histological analysis, colorimetric assay and ELISA, respectively, after FITC challenge. Results: DC migration and FITC-specific lymph node cell proliferation and cytokine production were normal in the AR-deficient mice. Ear swelling, tissue MPO and EPO activities and FITC-specific serum Ig levels were also similar in AR-deficient and -sufficient mice. Conclusions: Amphiregulin is not essential for the induction of FITC- or DNFB-induced CHS responses in mice. KEY WORDS: amphiregulin, contact dermatitis, EGF, mast cells, Th2 cell/cytokine